Syrona: an open-source visual analytics tool for pairwise comparison of health datasets in OMOP CDM - M. Pajusalu; M. Oja; K. Mooses; S. Heinsar; T. Laisk; G. Grents; T. Tillmann; S. Laur; S. Reisberg; J. Vilo; R. Kolde (BMC Medical Informatics and Decision Making, 2026)
Abstract Background Health research increasingly relies on observational datasets that capture systematically different patient populations, affecting the representativeness, comparability, and transportability of study findings. Yet these differences are rarely quantified across clinical domains or explored interactively, and the workflow for pairwise dataset comparison remains fragmented. No existing OHDSI tool provides an integrated visual analytics workflow for exploratory pairwise comparison of concept prevalence patterns between datasets on the OMOP Common Data Model. Results We present Syrona, an open-source visual analytics tool for systematic pairwise comparison of datasets and subcohorts on the OMOP Common Data Model. Syrona extracts annual prevalence for conditions, procedures, and drugs from any OMOP CDM database, computes prevalence ratios across demographic strata, and synthesizes them via multilevel meta-analysis. A coordinated dashboard - distributional overviews, stratified heatmaps, forest plots, and absolute prevalence comparisons - enables interactive exploration driven by domain-adaptive SNOMED CT and ATC filtering. Three case studies on Estonian national health data (495,000 persons, 2012–2024) demonstrate how the tool supports representativeness assessment, institutional practice comparison, and coding artifact detection. Conclusions Syrona is open-source and applicable to any OMOP CDM database. By treating dataset comparison as a visual analytics problem rather than a tabular reporting task, it addresses a gap in the OHDSI ecosystem and supports systematic assessment of datasets in distributed observational research.